Ask questions, get sales : close the deak and create long-term relationships - Schiffman, Stephan (Avon, Mass. : Adams Media, 2005)
In Ask Questions, Get Sales, the author and sales guru Stephan Schiffman helps readers boost their careers to the gold-medal level by teaching them how to strengthen their questioning skills during the sales process. The premise is simple yet effective: In order to be successful, salespeople need to change their mindset from "need-orientated" to "do-orientated". The message of the book centers around six core "do" questions: What do you do? How do you do it? When and where do you do it? Why do you do it that way? Who do you do it with? How can we help you do it better? With this indispensable guide in their briefcase, salespeople will have information at the ready to score big sales over the short term and the long term.
Getting started -- The most important question you can ask -- The six basic questions and the objectives behind them -- Silver, bronze, and gold -- The sales cycle -- The interviewing phase : techniques that work -- The past--by means of the future -- The present -- The future -- Verification and proposal development -- Questions to ask yourself.
Includes index.
Keywords: Selling